(untitled) (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
In this paper we deal with the issue of transnational literature using the case of the author of Bosnian origin Elvira Mujčić who, as a representative of the so-called second generation of immigrant writers in Italy, writes and publishes exclusively in Italian. The paper pays special attention to the issue of language in the construction of identity, which the author deals with in one of her most important novels, La lingua di Ana. Chi sei quando perdi radici e parole. If we accept in theoretical terms one of the basic principles of transnational locational feminism (for which Susan Stanford Friedman, literary critic and author of the influential study Mappings, is credited) stating that a literary text creates theory, the novel Ana’s Language can be considered a programmatic work that explores the question of language and its connection with identity, but also with the Other. The dominant idea in the novel is the coexistence of two languages as a possibility for creating a relationship with the Other, one that is different from us, which enables the fluidity of the heroine’s identity, but also her rejection of binary categories of existence, which is in line with the basic settings of locational feminism. As we will try to show in the paper, the host’s language has the additional function of rebirth after her traumatic exile from the language of her origin. As Elvira Mujčić is also actively involved in literary translation, we will consider her essay with the symbolic title “L’Altra”, in which she explains her own understanding of the coexistence of two languages, and the meaning and function of translation. Also, this paper tries to point out the need for a further mapping of diasporic literary voices, as well as the need for considering the status and recognition of female and male writers in the host country.